Kajian Pengembangan Wisata Bahari Di Kabupaten Banggai Kepulauan - Roberto Patar Pasaribu; Aris Kabul Pranoto; Chrisoetanto Pattirane (Jurnal Airaha, 2022)
The development of marine tourism is essentially an effort to develop and utilize marine tourism objects and attractions in coastal and ocean areas, in the form of beautiful natural wealth, diversity of flora and fauna. and beach recreation. Based on secondary data and direct observations, it shows that in the Banggai Islands there is a very large marine tourism potential, namely the attractiveness of beaches, coasts, islands and underwater biodiversity. The purpose of this study is to provide an overview of the potential conditions for marine tourism in the Banggai Islands and create a concept for developing marine tourism for the area. This study also seeks to make an inventory of the existing marine tourism potential by providing potential data, both biological-non-biological and social and cultural uniformity as a supporting attraction for the development of marine tourism. The analysis is carried out using a SWOT analysis to see the strengths, weaknesses, opportunities and threats in the development of marine tourism. From the SWOT analysis, it was found that the marine tourism area in the Banggai Islands can be developed because it has internal strengths, namely it has a lot of potential for marine tourism and there are opportunities, namely the existence of routine sea transportation routes and marine tourism routes that pass through the area.